Atorvastatin Increases ecNOS Levels in Human Platelets of Hyperlipidemic Subjects - Tannous, Marie; Cheung, Raphael; Vignini, Arianna; Mutus, Bulent (Thrombosis and Haemostasis, 1999)
Background. The purpose of this study was to probe the pleiotrophic effects of Atorvastatin on intraplatelet-nitric oxide metabolism. Methods and Results. Hyperlipidemic subjects (n = 19) were treated for 1 month (following a 3-week washout) with either Atorvastatin or placebo in a double-blinded randomized (n = 2, crossover), placebo-controlled study. Changes in the levels of intraplatelet nitric oxide synthase, nitrotyrosine were correlated with cholesterol, LDL-C, HDL-C and triglyceride levels. These studies indicate that with atrovastatin ecNOS levels increased on average by ~1.7-fold (paired t-test p = 0.009). Interestingly, levels of nitrotyrosylated platelet proteins, an indication of peroxynitrite damage, decreased as ecNOS levels increased in presence of the drug (paired t-test p = 0.33). Atorvastatin, at 10 mg per day, lowered cholesterol and LDL-C levels in all patients with the average lowering of ~21% and ~17% respectively. The effect on HDL was not significant whilst triglyceride levels were lowered by an average of ~18%. Conclusions. This study adds to the volume of evidence that statins have beneficial effects other than lipid lowering. Here, Atorvastatin is shown to significanly elevate intraplatelet ecNOS levels in hyperlipidemic subjects without affecting iNOS expression. The net result of this would be the elevation of NO production which would promote platelet deaggregation and vasodilation.
Keywords: Atorvastatin; nitric oxide synthase; intraplatelet; hyperlipidemia